Perubahan penggunaan lahan dengan data Nighttime Light pada kawasan terdampak gempa di Kabupaten Klaten - Muhammad Azmi Syarifuddin; Nur Miladan; Mochamad Primasakti Satyagraha (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
Increasing population density and regional development activities have intensified land demand for residential, commercial, and industrial uses. In disaster-prone areas, post-disaster land use dynamics are a critical issue in risk-based regional development planning. Klaten Regency is one of the regions affected by the 2006 earthquake and has undergone long-term reconstruction and socio-economic recovery processes. This study aims to analyze post-earthquake land use changes in Klaten Regency, particularly in affected areas, by utilizing Nighttime Light (NTL) data as a proxy for human activity and regional development. A deductive quantitative approach was applied using numerical analysis based on satellite-derived NTL data and spatial overlay techniques. The analysis focused on identifying changes in light intensity to represent land use dynamics and the concentration of post-reconstruction development. The results reveal a significant increase in light intensity in several areas, particularly in Central Klaten, reflecting growth in economic activities and infrastructure development. The observed pattern indicates a shift of community activities toward moderately and severely affected zones, with a predominance in moderately affected areas. These findings suggest that earthquake-affected areas continue to develop over time despite existing disaster risks. Therefore, risk-based regional development policies are essential to guide future growth toward safer and more sustainable zones.